A controller based on coefficient diagram method for the robotic manipulators - Uçar, A; Hamamci, SE (Ieee, 2000)
In this paper a controller based on coefficient diagram method is introduced developed for robotic manipulators. The significant property of this controller is the designer can design the controller simultaneously taking a good balance of stability, response, and robustness. The closed loop performance is illustrated for a manipulator with a bounded disturbance.
7th IEEE International Conference on Electronics, Circuits and Systems -- DEC 17-19, 2000 -- JOUNIEH, LEBANON